Мовностилістичні засоби реалізації авторської прагматики у романі Девіда Ніколлса «One day» - Маєвська, Наталія Михайлівна; Maіevska, N. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано мовностилістичні засоби реалізації авторської прагматики в романі Девіда Ніколлса «One day». Постмодерністське письмо є невичерпним джерелом образності й презентує багатий арсенал мовних засобів, які потребують системного лінгвістичного дослідження. Мета статті – прагмалінгвістичний аналіз мовностилістичних засобів реалізації авторської прагматики. Карнавалізація, інтертекстуальність, антономазія дають змогу читачеві стати свідком внутрішньої, психологічної діяльності персонажів та є потужними засобами створення прагматичного потенціалу постмодерністських романів. The article deals with linguistic and stylistic features of pragmatics in the novel by David Nicholls «One day». Postmodern writing is an inexhaustible source of imagery and presents rich material for systematic linguistic research. The purpose of the article is prahmalinhvistyc analysis of linguostylistic means of authoring pragmatists. Postmodernists encourage the reader for considered reading, giving information implicitly, through various stylistic devices. David Nichols keeps in his work a documentary tone, using the best techniques of postmodernism: sharp transitions, changing positions of storytellers, modes of transmission events in the form of recording telephone conversations, letters, fragments of memories, «technique of one day» and intertextuality. Carnivalization, intertextuality and antonomaziya allow the reader to witness the internal psychological activity and are powerful tools of creating pragmatic potential of postmodern novels.
Linguistic and Stylistic Features of Pragmatists in the Novel by David Nicholls «One day»
Keywords: постмодернізм; postmodernism; прагматика; pragmatics; карнавалізація; carnivalization